Psychological Legacy and Identity Crisis in Ralph Ellison’s Invisible Man and Juneteenth - Othman, Abdelrahman Jalal; Zainalddin, Rebwar (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
There has been an increased interest in the study of both identity and psychology in literary studies especially in the second half of the twentieth century to the present day. This paper deals with the crisis of identity and the accompanying psychological conditions in Ralph Ellison’s novels Invisible Man and Juneteenth. The study will highlight how the main characters in these works face difficult choices in facing the reality of life in a society that is affected by cultural and racial prejudice. Ellison himself belonging to the race, tries to depict the agonies of African Americans who despite of being contributors to the foundation of the nation yet, they have been denied the status of visibility. Through sharing the traumatic experiences of his protagonists, Ellison is trying to uncover some real issues that many people thought they have been bypassed in the so-called developed country as The United States.